Inequality in Indonesia: Kuznets Waves or Kuznets Curve? - Wardhana, Dharendra (Bappenas Working Papers, 2020)
This paper sets out an argument that Kuznets hypothesis—either Kuznets curve or Kuznets waves—is testable and might not hold depending upon the context. In order to better understand the proposition of Kuznets and its relevance to Indonesia, it is necessary to consider what happens across long periods of time (la longue durée) and to comprehend how watershed events affect the economy and the distribution of wealth. Analysis in this paper rely on various data sources ranging from conventional economic indicators, historical archives, to literary works. Fluctuation on Gini index in Indonesia might not be fully explained with Kuznets hypothesis although several aspects might influence inequality trends.